50 Years of Urbanization in Africa : Examining the Role of Climate Change - Henderson, J. Vernon; Storeygard, Adam; Deichmann, Uwe (World Bank, Washington, DC, 2014)
This paper documents a significant impact of climate variation on urbanization in Sub-Saharan Africa, primarily in more arid countries. By lowering farm incomes, reduced moisture availability encourages migration to nearby cities, while wetter conditions slow migration. The paper also provides evidence for rural-urban income links. In countries with a larger industrial base, reduced moisture shrinks the agricultural sector and raises total incomes in nearby cities. However, if local cities are entirely dependent on servicing agriculture so their fortunes move with those of agriculture, reduced moisture tends to reduce local urban incomes. Finally, the paper shows that climate induces employment changes within the rural sector itself. Drier conditions induce a shift out of farm activities, especially for women, into non-farm activities, and especially out of the workforce. Overall, these findings imply a strong link between climate and urbanization in Africa.